Modern researches on Blood Stasis syndrome 1989–2015: A bibliometric analysis. Issue 49 (December 2016) - Liao, Jiangquan; Wang, Jie; Liu, Yongmei; Li, Jun; Duan, Lian; Chen, Guang; Hu, Junyuan
Abstract: Background: Blood Stasis syndrome (BSS) is one of the major syndromes in Traditional East Asia medicine (TEAM). Modern research of BSS began in the late1980s. Methods: We searched in PubMed for BSS-related articles published between 1989 and 2015. The publication information, study contents, and bibliometric indicators were documented and analyzed. Results: Most of the BSS-related studies were conducted by Chinese researchers in China. The number of publications on BSS-related increased rapidly in recent years, so did the quality of them. The disease diversity of BSS-related studies increased along with the number of publications. Yet the academic influence of them remained on average low; further, the diagnostic criteria of BSS were not uniform. Conclusions: BSS-related studies have increased in quantity and quality, but there are limitations to them which require improvement in research productivity and academic influence.